Change of the cognitive matrix for the formation of the person in Ecuador - Aguilar Gordón, Floralba del Rocío (2020)
The present article reflects on the curriculum and cognitive matrix of the educational model that currently rules the Ecuadorian education, taking as reference the personalist vision of Gabriel Marcel. The document proposes to rethink the different dimensions of the educational activity emphasized in the main postulates of personalism that allows the revaluation of the man and of the education, promoting centrality of the individual versus pragmatic training, economist and consumerist, which as ultimate purpose has promulgated today’s society. This work consists of three parts: the first analyzes the anthropological vision that guides current Ecuadorian education, taking as reference some postulates expressed in the National Plan for Good Living 2013-2017 and the National Development Plan 2017-2021. Toda una vida with different postulates established in the Constitution of the Republic of Ecuador of 2008, in the Organic Law of Higher Education and other regulations related to the educational proposal. The second part reflects on Gabriel Marcel’s personalist proposal and its implications in the Ecuadorian educational work and in the integral formation of the human being, having the person as fundamental center of social development. The third part analyses the advantages and disadvantages of an anthropological proposal for the integral education in Ecuador.